2019
DOI: 10.1097/md.0000000000015454
|View full text |Cite
|
Sign up to set email alerts
|

Good hemostatic effect of platelets stored at 4°C in an in vitro model of massive blood loss and thrombocytopenia

Abstract: This study compared the corrective effects of storage of platelets at 4°C and at 22°C in an in vitro model of massive blood loss and thrombocytopenia to provide an experimental basis for the storage of platelets for clinical applications. In vitro model of massive blood loss and thrombocytopenia were constructed by the in vitro hemodilution method and cell washing method. Using storage of platelets at 4°C (1, 3, 5, 7, 10, 14 days) and at 22°C (1, 3, 5 days) to correct the coagulation condition of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Alternatively, refrigeration of platelets at 4°C allows storage for up to 14 days yielding significantly higher metabolic reserves, agonist-induced functional responses in vitro, and clot strength compared to RTP. [11][12][13][14][15][16][17][18][19][20][21] Furthermore, these cold-stored platelets (CSP) are responsive to physiological inhibitors, 18,22 with in vivo bleeding correction times similar to fresh platelets. 11,20 In our previous efforts to investigate the mechanical and structural properties of clots formed from banked platelets, we reported that CSP formed clots with stiffness and strength comparable to fresh platelets, and that clots from RTP showed the effects of compromised contractile function on fibrin morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, refrigeration of platelets at 4°C allows storage for up to 14 days yielding significantly higher metabolic reserves, agonist-induced functional responses in vitro, and clot strength compared to RTP. [11][12][13][14][15][16][17][18][19][20][21] Furthermore, these cold-stored platelets (CSP) are responsive to physiological inhibitors, 18,22 with in vivo bleeding correction times similar to fresh platelets. 11,20 In our previous efforts to investigate the mechanical and structural properties of clots formed from banked platelets, we reported that CSP formed clots with stiffness and strength comparable to fresh platelets, and that clots from RTP showed the effects of compromised contractile function on fibrin morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Functional losses owing to the platelet storage lesion and increased risk of microbial contamination over time compromise platelet shelf life. Alternatively, refrigeration of platelets at 4°C allows storage for up to 14 days yielding significantly higher metabolic reserves, agonist‐induced functional responses in vitro, and clot strength compared to RTP 11–21 . Furthermore, these cold‐stored platelets (CSP) are responsive to physiological inhibitors, 18,22 with in vivo bleeding correction times similar to fresh platelets 11,20 …”
Section: Introductionmentioning
confidence: 99%
“…(3) patients exhibiting platelet transfusion indications, including: massive blood loss(massive blood loss is replacement of the patient's total blood volume or transfusion of more than ten units of blood within 24 hours;A replacement of 50% of circulating blood volume in less than three hours or more than 150 ml per minute. ); platelet count ≤ 50×10 9…”
Section: Inclusion Criteriamentioning
confidence: 99%